Revealing the Unusual Behavior of Rhenium (I) Tricarbonyl Complex Functionalized with Aza-Macrocycles in Response to Metal Ions - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A (Elsevier B.V., 2025)
Three new rhenium phenanthroline tricarbonyl complexes were synthesized and fully characterized to examine changes in their photophysical properties and spectroscopic behavior in the presence of metal ions. To achieve this, the complexes were designed with modifications in both the phenanthroline and the axial ligand. The 4,7–dichloro–1,10–phenanthroline (Cl2phen) precursor was functionalized with two units of 1–aza–15–crown–5 (1A15C5) to obtain the complex [Re((A15C5)2phen)(CO)3Br] (1) with the aim to study the spectroscopic perturbations induced by the binding of the metal ions by this receptor. Interestingly, the rhenium complex 1 shows a particular behavior towards Hg(II) and Pb(II), as a result of the halide abstraction assisted by these metal ions. Additionally, in the presence of Cu(II) the interaction and coordination/binding with the macrocycle cavities is also presumed. The chemical reaction assisted by Hg(II) was confirmed by changes in the absorption, emission and FT–IR spectra of [Re(Cl2phen)(CO)3Br] (2) in presence of the heavy metal ion. These obtained profiles had similar patterns to the ones shown by the cationic complex [Re(Cl2phen)(CO)3(CH3CN)]PF6 (3). As final confirmation, this last complex was also studied in the presence of metal ions and its spectra remained unaltered. © 2024 Elsevier B.V.